Implementasi Kebijakan Pentingnya Penguatan Pendidikan dalam Membentuk Peserta Didik Karakter di Sekolah Dasar Muhammadiyah 5 Pekanbaru - Ayu Lestari; Lidya Zanti; Wan Elnayla Azzahra Reza; Windi Alya Ramadhani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Character education plays a crucial role in shaping students who excel not only academically but also possess strong moral and social values. In this regard, the government, through the Ministry of Education and Culture, has launched the Strengthening Character Education (PPK) policy as a strategic step to create a generation of character. This study aims to explore how the PPK policy is implemented in elementary schools and analyze the factors that support and hinder its implementation. The method used in this study is descriptive qualitative, with data collection techniques through observation, in-depth interviews with principals and teachers, and documentation studies. The results show that the PPK policy has been implemented through the integration of character values into the learning process, extracurricular activities, and school culture. Several factors supporting the success of this implementation include the principal's visionary leadership, active teacher involvement, and support from parents and the community. However, several challenges remain, such as a lack of supporting facilities, uneven teacher training, and difficulties in consistently integrating character values across all subjects. Overall, the PPK policy in elementary schools has had a positive impact on student character development, although further strengthening is still needed in terms of training, evaluation, and collaboration between all stakeholders. Supporting factors for successful implementation include the visionary leadership of the principal, active teacher involvement, and support from parents and the community. However, several obstacles remain, such as a lack of supporting facilities, uneven teacher training, and difficulties in integrating character values consistently across all subjects. Overall, the PPK policy in elementary schools has had a positive impact on student character development, although further strengthening is needed in terms of training, evaluation, and synergy between stakeholders.